Container model of a multi-component system in the digital twin architecture - Alkema, V.V. (Problems of Informatization and Management, 2025)
The paper addresses the problem of formal modeling of multi-component computer systems within the architecture of digital twins. The relevance of the study is обусловлена the rapid development of container technologies, microservice architectures, and distributed computing environments where systems consist of numerous interacting components. A container-based model of a multi-component system is proposed in which a container is interpreted as a structural and functional subsystem with a defined state space, dynamic operator, and resource characteristics. The system is represented as a set of interacting containers, for which the interaction mechanisms, local component dynamics, and resource constraints are formally defined. An aggregated model of the global system dynamics is constructed, enabling system-level analysis of behavior. Within the digital twin architecture, a mapping between the physical system and its digital representation is introduced, and conditions of structural, dynamic, and resource consistency are formulated. The proposed approach integrates container-based decomposition with a mathematical representation of system behavior and can serve as a formal basis for digital twin architectures in distributed, cloud, and edge computing environments.